Optimization of the Parameters Affecting the Fenton Process for Decolorization of Reactive Red 198 (RR-198) from the Aqueous Phase - Mansooreh Dehghani; Mahshid Ghadami; Talat Gholami; Marzieh Ansari Shiri; Zahra Elhameyan; Mohammad Reza Javaheri; Narges Shamsedini; Samaneh Shahsavani (Shiraz University of Medical Sciences, 2015)
Background: Recently, there has been a great concern about the consumption of dyes because of their toxicity, mutagenicity, carcinogenicity, and persistence in the aquatic environment. Reactive dyes are widely used in textile industry. Advanced oxidation processes are one of the cost-effective methods for the removal of these dyes. The main aims of this study were determining the feasibility of using Fenton process in removing Reactive Red 198 (RR-198) dye from aqueous solution and determining the optimal conditions. Methods: This is a cross-sectional study conducted at a laboratory scale. A total of 69 samples were considered and the effect of pH, Fe (II) concentration, H2O2 concentration, initial dye concentration and reaction time were investigated. Results: According to the results, a maximum removal efficiency of 92% was obtained at pH of 3 and the reaction time of 90 min; also, the concentration of Fe (II), H2O2, initial dye concentration were 100 mg/L, 50 mg/L, and 100 mg/L, respectively. The results revealed that by increasing the concentration of Fe (II), H2O2 and initial dye, the removal efficiency was increased. Conclusions: The results showed that Fenton process could be used as a cost-effective method for removing RR-198 dye from textile wastewater efficiently.